Decision Support System for Selection of Scholarship Recipient Students Using Tsukamoto Method Fuzzy Logic - Anwar, Mufti Husain; Furqan, Mhd.; Suhardi, S (Sekolah Tinggi Ilmu Komputer (STIKOM) Tunas Bangsa, 2024)
Scholarship selection is an important process in determining the acceptance of educational assistance based on established criteria. Decision Support Systems (DSS) have proven their value in assisting complex decision making. In the context of scholarship selection, Tsukamoto's fuzzy approach in decision support systems is an effective tool for modeling the complexity and uncertainty of selection criteria. This system utilizes fuzzy logic to connect variable inputs such as academic achievement, financial condition, and other factors to output in the form of membership values in the scholarship acceptance category. The fuzzy rules defined by educational experts and practitioners enable the system to interpret conditions that are closer to human thinking. Thus, Tsukamoto's fuzzy approach in decision support systems becomes an effective tool in simplifying the complexity of scholarship selection, while providing data-based solutions. More objective and comprehensive.